The Value of Neurological Assessment for Prediction of Subtle Cerebral Infarction. (29th March 2021) - Horev, Anat; Serlin, Yonatan; Eshel, Ron; Leker, Ronen; Star, Michael; Honig, Asaf; Ifergane, Gal
ABSTRACT: We examined to what extent clinical assessment alone can predict subtle acute cerebral infarction on magnetic resonance imaging (MRI). Of the 72 patients presented to the emergency department (ED) with transient neurological deficits, 26 (36.1%) were predicted to be "positive" and 46 (63.9%) "negative" for transient ischemic attack/minor stroke by two independent neurologists. Twenty patients (27.8%) had acute restricted diffusion on MRI. Clinical assessment showed substantial agreement with MRI findings (Kappa = 0.75), sensitivity (95.0%), specificity (86.5%), positive-likelihood ratio 7.06, and negative-likelihood ratio 0.06. Neurological assessment has an excellent predicting value for MRI-confirmed acute cerebral infarction and a key role in the facilitation of effective patient care in the ED.